Charged Gold Nanoparticles Promote In Vitro Proliferation in Nardostachys jatamansi by Differentially Regulating Chlorophyll Content, Hormone Concentration, and Antioxidant Activity - Shubham Joshi; Aqib I. Dar; Amitabha Acharya; Rohit Joshi (MDPI AG, 2022)
Nardostachys jatamansi is a critically endangered medicinal plant and endemic to the Himalayas, having high commercial demand globally. The accumulation of various secondary metabolites in its shoots and roots with antioxidant potential are well-documented in traditional as well as modern medicine systems. In the present study, we first attempted to investigate the impact of citrate (−ve charge, 11.1 ± 1.9 nm) and CTAB (+ve charge, 19.5 ± 3.2 nm) coated gold nanoparticles (AuNPs) on the in vitro proliferation and antioxidant activities of N. jatamansi. Both the nanoparticles differentially affected the morphological and biochemical parameters, chlorophyll content, internal hormone concentration, and antioxidant activities in a concentration-dependent (10-100 µM) manner. Vigorous shooting was observed in half strength MS medium supplemented with IAA (1 mg/L) with 60 µM citrate-AuNPs (46.4 ± 3.7 mm) and 40 µM CTAB-AuNPs (42.2 ± 3.2 mm). Similarly, the maximum number of roots (5.00 ± 0.67 and 5.33 ± 0.58) and root length (29.9 ± 1.5 mm and 27.3 ± 4.8 mm) was reported in half-strength MS medium with IAA (1 mg/L) supplemented with 60 µM citrate-AuNPs and 40 µM CTAB-AuNPs, respectively. In addition, plants growing on MS medium supplemented with 60 µM citrate-AuNPs and 40 µM CTAB-AuNPs showed significantly enhanced photosynthetic pigments (chlorophyll a and b, carotenoids, and total chlorophyll), internal hormone concentration (GA3, IAA, and ABA), and antioxidant activities (total phenolics, flavonoids, DPPH, and SOD enzyme activity). Moreover, the transcript analysis of ANR1, ARF18, PLY9, SAUR28, GID1A, GRF1, SOD, and CAT further confirmed the role of 60 µM citrate-AuNPs and 40 µM CTAB-AuNPs in the improvement in the growth and antioxidant activities of N. jatamansi. Bearing in mind the urgent requirements of the effective conservation measures of this endangered species, the present findings suggest the elicitation of citrate-AuNPs and CTAB-AuNPs would significantly improve the potential applications of N. jatamansi in the medicinal plant-based industry.